2021
DOI: 10.18332/tpc/134800
|View full text |Cite
|
Sign up to set email alerts
|

Readiness for implementation of smoke-free work hours in private companies: A qualitative study of perceptions among middle managers

Abstract: INTRODUCTION Workplaces are important settings for implementation of smoke-free environments. In this study, we follow a medical production company with 677 employees that implemented one of the most stringent tobacco policies legally possible in Denmark -smoke-free work hours -which means that employees are not allowed to smoke during work time. This study explores tobacco use restrictions during work hours regarding readiness of implementation, focusing specifically on middle managers' perceptions and consi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 32 publications
(43 reference statements)
0
3
0
Order By: Relevance
“…In addition to limited knowledge about smoke-free policies and the dangers of SHS, several studies cited a lack of training for stakeholders responsible for policy enforcement (e.g. law enforcement, hospital staff) as a barrier to enforcing smoke-free policies 21,27,44,108 . For example, one study of middle managers in a private company in Denmark found that, while middle managers supported smoke-free policies, they did not feel they were responsible for 'regulating other peoples' actions' and did not feel adequately prepared to address violations and discuss smoking cessation with their employees 108 .…”
Section: Stakeholder Trainingmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to limited knowledge about smoke-free policies and the dangers of SHS, several studies cited a lack of training for stakeholders responsible for policy enforcement (e.g. law enforcement, hospital staff) as a barrier to enforcing smoke-free policies 21,27,44,108 . For example, one study of middle managers in a private company in Denmark found that, while middle managers supported smoke-free policies, they did not feel they were responsible for 'regulating other peoples' actions' and did not feel adequately prepared to address violations and discuss smoking cessation with their employees 108 .…”
Section: Stakeholder Trainingmentioning
confidence: 99%
“…law enforcement, hospital staff) as a barrier to enforcing smoke-free policies 21,27,44,108 . For example, one study of middle managers in a private company in Denmark found that, while middle managers supported smoke-free policies, they did not feel they were responsible for 'regulating other peoples' actions' and did not feel adequately prepared to address violations and discuss smoking cessation with their employees 108 . Thus, training for enforcement stakeholders that discusses the extent of their roles and responsibilities, protocol for responding to violations, and (in healthcare settings) providing smoking cessation services, can potentially increase compliance 27,44,66,68,73,74,95,108,109 .…”
Section: Stakeholder Trainingmentioning
confidence: 99%
“…In the Danish context, smoke-free work hours include all tobacco-related products, that is, all tobacco and nicotine products (except medicinal nicotine replacement therapy) and other related products such as e-cigarettes without nicotine. Thus, the smoke-free work hours strategy is a much stricter prevention method than other strategies and is to our knowledge an unevaluated Scandinavian phenomenon 12 .…”
Section: Introductionmentioning
confidence: 86%